Effect of sesame seeds or oil supplementation to the feed on some physiological parameters in Japanese Quail - N.E. Mohamed; M.M. Wakwak (Journal of Radiation Research and Applied Sciences, 2014)
A total No. of 200 three weeks old Japanese quail from the breeding flock in the Poultry Research Farm of Nuclear Research Center, Atomic Energy Authority, Cairo, Egypt, were used in this study. The quail chicks were randomly allotted equally to five groups (40 birds per each). For 4 weeks experimental period birds were kept in battery cages and water and feed were provided ad libitum. A basal diet of 24% protein and 3000 kcal M.E./Kg was formulated to cover all nutrients needed. The experimental design included five tested groups as follows: group (1): birds fed on the basal diet and served as control. Group (2): birds fed on the basal diet supplemented with 2% sesame seeds. Group (3): birds fed on the basal diet supplemented with 4% sesame seeds. Group (4): birds fed on the basal diet supplemented with 2%sesame oil. Group (5): birds fed on the basal diet supplemented with 4% sesame oil. The effect of sesame seeds or oil supplementations in feed on some physiological parameters in Japanese quails was investigated. It was observed that the groups of quails supplemented with 4% sesame seeds or 4%oil recorded the lowest body weight. Female and male carcass weight had significant increase in group supplemented with 4% oil as compared to the control group. Total lipids in the eggs significantly decreased in group supplemented with 4% oil as compared to the control group. Cholesterol content in the eggs significantly decreased in group supplemented with 4% sesame seeds while triglycerides in the eggs recorded significant decrease in the group supplemented with 2% sesame seeds. Eggs weight did not significantly change due to the feeding on sesame seeds or oil but, the group supplemented with 4%seeds laid higher number of eggs than other groups. Serum total protein, albumin, alanine transferase, aspartate transferase, alkaline phosphatase, gamma glutamyl transferase, urea, creastinine, total triiodothyronine (T3) and total thyroxin(T4) concentrations were with the normal level as compared to the control group. Blood components of liver and kidney functions are normal in all experimental groups. Total lipids and triglycerides in female and male groups supplemented with 4% sesame seeds significantly decreased as compared to the control group while serum cholesterol level in both female and male groups supplemented with 2% sesame seeds decreased significantly as compared to the control group. Thiobarbituric acid reactive substances (TBARS) significantly decreased in spleen and bursa homogenates in both female and male group supplemented with 4%oil. Glutathione content in spleen increased significantly in female and male groups supplemented with 4% oil as compared to the control group. While catalase increased significantly in group supplemented with 2%oil in spleen homogenate. Glutathione content in bursa homogenate was significantly increased in female group supplemented with 2%oil while in male group supplemented with 4%oil as compared to the control group. Catalase content in bursa homogenate increased significantly in both female and male group supplemented with 4%oil. Histological examination of ileum section showed long villi in group supplemented with 2% oil and other sections showing activation of mucous secreting cells lining intestinal villi in group supplemented with 4% oil. It could be concluded that sesame oil 2% or 4% supplementation to the feed can improve physiological performance of quails.